ASAS PELAKSANAAN LAYANAN KONSELING DALAM PROGRAM BIMBINGAN DAN KONSELING DI SEKOLAH - Shifa, Nabilla Nur; Sunarti, Titi; Amanda, Novia; Raisya, Putri; Ulwiyah, Shilfa Muhimatun (Jurnal Merah Putih Sekolah Dasar, 2025)
This article discusses the ideas and principles of guidance and counseling as guidelines for counselors in implementing school-based services. Applying these principles helps improve program effectiveness and supports students in understanding themselves better. The principles serve as a foundation to ensure that counseling services are conducted consistently, meet established standards, and help individuals make appropriate decisions. Key principles include openness, voluntariness, independence, dynamism, integration, normativity, professionalism, and tut wuri handayani. Overall, these principles provide practical recommendations to ensure that guidance and counseling services are delivered ethically, effectively, and in accordance with students’ developmental needs.